Os efeitos do programa de estimulação e a variável sexo no desempenho em consciência fonêmica - Moura, Simone Raquel Sbrissa (2008)
Abstract 1: This study focuses on phonemic awareness in relation to the performance between boys and girls, and programs of stimulation. A critical review of the literature was carried out, seeking so summarize the main studies on this theme. Various studies were found which address phonological awareness as a whole, and which present different findings in relation to the sex variable. Few stimulation programs focus on specific skills, particularly phonemic awareness. All the models of intervention in phonological awareness show significant results in relation to performance and learning of reading-writing. In some studies, a lack of clarity is observed concerning the precise definition of the terms “phonological awareness” and “phonemic awareness”. Therefore, regardless of the differences between the sexes, programs aimed at stimulating phonological awareness are an important form of contributing to the clinical and educational area. However, there is a need for more studies to investigate the skills at the phoneme level. Abstract 2: Purpose: To determine the influence of the sex variable in phonemic awareness tasks. Methods: The sample consisted of 36 students in the second grade of Elementary School: 18 boys and 18 girls. All were submitted to audiological screening, speech therapy assessment, and assessment of phonetic awareness skills. Results: In general, the statistical analysis did not reveal any significant differences between the sexes. However, in qualitative terms, it was observed that the girls were more successful than the boys, in all the phoneme ‘segmentation’ and ‘synthesis’ tasks, which affected the analysis of smaller elements. Conclusions: Although no statistically significant differences were observed between the sexes, it was observed that the girls performed better in the phonemic awareness skills. Abstract 3: Background: stimulating phonemic awareness and comparing its effects between the sexes. Aim: to determine the possible gain in performance in tasks involving phonemic awareness skills in boys and girls, following the development of a program to stimulate phonemic awareness. Method: the sample consisted 18 boys and 18 girls, all with typical development, in their second grade of Elementary Education. The study consisted of three stages. In the first and last stages consisted of the audiological screening, hearing and speech therapy assessments and assessments of phonemic skills, through the Phonological Awareness Tasks Protocol. In the intermediary phase, the program to raise phonemic awareness was planned in advanced, then applied in the classroom, with the pupils and teachers. Results: boys and girls showed better performance after the development of the program to stimulate all the phonemic awareness tasks, with a statistically significant difference. In relation to the influence of the sex variable, it was observed that before the program, there was a significant difference between boys and girls in the task to "detect the phoneme in the final position". After stimulation, this difference remained significant in the same task, and was also statistically significant for the tasks of “phonemic segmentation of words with six phonemes” and “phoneme reversion for words with two or three phonemes". Conclusion: it is concluded that the girls performed better in the majority of the phonemic awareness tasks, and that the program effectively stimulated these tasks.